Efektivitas Revitalisasi Pasar Sentral dan Dampaknya Terhadap Pendapatan Pedagang di Kota Gorontalo - Sune, Ramadhita Pratiwi; Canon, Syarwani; Payu, Boby Rantow (PPJP ULM, 2024)
This study aims to determine: the level of effectiveness of the market revitalization program seen from the aspects of input, process, and output; the level of customer satisfaction after the implementation of the market revitalization program; differences in market management before and after the revitalization program; changes in market environmental conditions before and after the revitalization program; and differences in income before and after the market revitalization program. his research was conducted in Gorontalo City Central Market with 87 traders and 51 buyers as respondents. This research used descriptive analysis technique and Wilcoxon test. The results showed that the effectiveness of the market revitalization program on input, process, output, and customer satisfaction variables was considered quite effective. The input variable reached an average value of 70.6%, the process variable reached 71.2%, the output variable reached 79.8%, and the customer satisfaction variable reached 72.4%. In addition, there are differences in the income level of traders after the revitalization program. The results of this study also show that there is a difference in the income level of traders after the revitalization program.